FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT MAHASISWA AKUNTANSI DALAM PEMILIHAN KARIR MENJADI SEORANG AKUNTAN PUBLIK - Divina Fitriana; Harti Budi Yanti (EBID: Ekonomi Bisnis Digital, 2023)
The  purpose  of  this  research  is  to  test  and  find  out  the  influence  of  accounting  students'  interest  in Financial  Awards,  Work  Environment,  social  values, and Labor  Market  Considerationson accounting students'  interest  in  becoming  professional  public  accountants  in  active  Bachelor  of  Accounting  studentsclass  of  2019at  Trisakti  University. This  research  is  a  type  of  quantitative  research. The  sampling technique of this research is purposivesamplingmetode, with the number of samples used as many as 100 samples. This  research  uses  multiple  linear  regression  method  using SPSS  version  25  as  a data  analysis technique. The result of the research shows that factors Financial Awards, Work Environment, and Labor Market Considerations have positive and significant affect on Accounting StudentsInterestin choosing a carrer  to  became  a  public  accountant.  While  the  social  values  has  negative  or  no  significant  affect  on Accounting Students Interest in choosing a carrer to became a public accountant